Pengaruh Metode Sistem Pencairan Dana Terhadap Kepuasan Penerima Dana Pensiun Asabri Cabang Medan - Hutagalung, Cristian Vebry; Purba, Melfrianti Romauli; Sitorus, Paskah Ria; Andari, Ayu (Jurnal Ekonomi Bisnis Manajemen Prima, 2023)
Abstract This research was conducted at PT.ASABRI (Persero) Medan Branch to find out how the fund disbursement system method affects the satisfaction of pension fund recipients by using both online and offline fund disbursement methods. This type of research is a descriptive research with a cumulative method. And the results of the study found that the fund disbursement system method carried out by PT. ASABRI has an influence on the satisfaction of pension fund recipients, this can be seen from the satisfaction of pension recipient customers with Qualitative descriptive method with 50 samples.